Is sham cTBS real cTBS? The effect on EEG dynamics - Opitz, Alexander; Legon, Wynn; Mueller, Jerel; Barbour, Aaron; Paulus, Walter; Tyler, William J. (Frontiers in Human Neuroscience, 2015)
Increasing sensitivity of modern evaluation tools allows for the study of weaker electric stimulation effects on neural populations. In the current study we examined the effects of sham continuous theta burst (cTBS) transcranial magnetic stimulation to the left dorsolateral prefrontal cortex (DLPFC) upon somatosensory evoked potentials (SEP) and frontal-parietal phase coupling of alpha and beta bands. Sham TMS results in an induced electric field amplitude roughly 5% that of real TMS with a similar spatial extent in cortex. Both real and sham cTBS reduced the amplitude of the frontal P14-N30 SEP and increased local phase coupling in the alpha-beta frequency bands of left frontal cortex. In addition, both sham and real cTBS increased frontal-parietal phase coupling in the alpha-beta bands concomitant with an increase in amplitude of parietal P50-N70 complex. These data suggest that weak electric fields from sham cTBS can affect both local and downstream neuronal circuits, though in a different manner than high strength TMS.